Risk factors and early markers for echovirus type 11 associated haemorrhage-hepatitis syndrome in neonates, a retrospective cohort study - Wang, Ping; Xu, Yi; Liu, Ming; Li, Huixian; Wang, Hui; Liu, Yumei; Wang, Bin; Xia, Shiwen; Su, Heng; Wei, Mou; Tao, Li; Chen, Xiaowen; et al. (Frontiers in Pediatrics, 2023)
Background Echovirus type 11(E-11) can cause fatal haemorrhage-hepatitis syndrome in neonates. This study aims to investigate clinical risk factors and early markers of E-11 associated neonatal haemorrhage-hepatitis syndrome. Methods This is a multicentre retrospective cohort study of 105 neonates with E-11 infection in China. Patients with haemorrhage-hepatitis syndrome (the severe group) were compared with those with mild disease. Clinical risk factors and early markers of haemorrhage-hepatitis syndrome were analysed. In addition, cytokine analysis were performed in selective patients to explore the immune responses. Results In addition to prematurity, low birth weight, premature rupture of fetal membrane, total parenteral nutrition (PN) (OR, 28.7; 95% CI, 2.8-295.1) and partial PN (OR, 12.9; 95% CI, 2.2-77.5) prior to the onset of disease were identified as risk factors of developing haemorrhage-hepatitis syndrome. Progressive decrease in haemoglobin levels (per 10 g/L; OR, 1.5; 95% CI, 1.1-2.0) and platelet (PLT) <140 × 10⁹/L at early stage of illness (OR, 17.7; 95% CI, 1.4-221.5) were associated with the development of haemorrhage-hepatitis syndrome. Immunological workup revealed significantly increased interferon-inducible protein-10(IP-10) (P <0.0005) but decreased IFN-α (P <0.05) in peripheral blood in severe patients compared with the mild cases. Conclusions PN may potentiate the development of E-11 associated haemorrhage-hepatitis syndrome. Early onset of thrombocytopenia and decreased haemoglobin could be helpful in early identification of neonates with the disease. The low level of IFN-α and elevated expression of IP-10 may promote the progression of haemorrhage-hepatitis syndrome.